A CZE-UV Method for Saturated and Unsaturated Fatty Acids Determination in Hops. (2nd January 2020) - Duarte, Lucas Mattos; Amorim, Tatiane Lima; Adriano, Luiz Henrique Cantarino; de Oliveira, Marcone Augusto Leal
Abstract: Fatty acids (FA) are minor compounds in beer and its raw materials, but can develop important roles in brewing and require monitoring. The aim of this work was to show the potential of capillary electrophoresis for fast hop analysis and to propose a simple method for the determination of saturated and unsaturated FA in different hop varieties. Sample preparation was investigated and evaluated and validation procedures were carried out to determine palmitic, stearic, oleic and linolenic FA in hops. Low values of relative standard deviation for areas (< 5.32%) and good recoveries (85-110%) were achieved. Laborious extraction and derivatization reactions were not necessary and only a saponification reaction was employed in sample preparation. Also, specific columns were not required and analysis time was only 10 min. The proposed methodology appears promising for faster monitoring of FA in terms of hop quality control in the brewing industry.